Secondary battery separator, its manufacturing method, and lithium secondary battery including the same

JP7640605B2Active Publication Date: 2025-03-05SK IE TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023065025
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-10-17
Filing Date
2023-04-12
Publication Date
2025-03-05
Estimated Expiration
2038-10-16

AI Technical Summary

Benefits of technology

【0026】 本発明の一態様による二次電池用セパレータは、低い熱収縮率および高い溶融破断温度などの熱的安定性が著しく向上するため、急激な温度上昇などの異常現象による発火や破裂を防止することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640605000001
    Figure 0007640605000001
  • Figure 0007640605000002
    Figure 0007640605000002
  • Figure 0007640605000003
    Figure 0007640605000003
Patent Text Reader

Abstract

To provide a separator for a secondary battery, a method of manufacturing the same, and a lithium secondary battery including the same.SOLUTION: The separator for a secondary battery includes a porous substrate and a coating layer formed on the porous substrate. The coating layer includes a plurality of inorganic particles, and a binder binding the plurality of inorganic particles. The binder includes a copolymer of a monomer mixture containing an acrylamide monomer, a vinyl cyan monomer, and an acrylic monomer having a carboxyl group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for a secondary battery, a method for producing the same, and a lithium secondary battery including the same. [Background technology]

[0002] In recent years, with the trend toward high capacity and high output of secondary batteries, there is an increasing demand for separators with high strength, high transmittance, thermal stability, and improved characteristics for the electrical safety of secondary batteries during charging and discharging. In the case of lithium secondary batteries, high mechanical strength is required to improve safety during the manufacturing process and use of the battery, and high transmittance and high thermal stability are required to improve capacity and output.

[0003] In addition, lithium secondary batteries are charged and discharged by repeating the process of lithium ions from the positive electrode being inserted into and removed from the negative electrode. When such charging and discharging is repeated, the theoretical capacity of the battery varies depending on the type of electrode active material, but in most cases, a problem occurs in that the charge and discharge capacity decreases as the cycle progresses.

[0004] In the case of polymer separators currently being mass-produced, research is being conducted to improve heat resistance and battery stability by mixing inorganic substances such as alumina in the form of a binder solution to improve thermal shrinkage, coating using wet methods such as die coating and dip coating, and then drying.

[0005] Conventionally, as one aspect of increasing the heat resistance of secondary battery separators, a process of forming a coating layer using a heat-resistant resin using an organic solvent has been applied. However, when an organic solvent is used, the process of recovering or incinerating the solvent after coating and drying reduces economic efficiency and is not environmentally friendly. In addition, since an organic solvent has excellent affinity with a microporous membrane, it has a property of being absorbed into the pores of the microporous membrane during the coating process. Due to this characteristic, when a coating layer is formed using a solution in which a heat-resistant resin is dissolved, the inside of the pores of the microporous membrane is coated with the heat-resistant resin after the drying process. The microporous membrane coated with the heat-resistant resin has a reduced pore size and a reduced permeability, and when the shutdown function of the microporous membrane is expressed at high temperatures, the shutdown is hindered by the heat-resistant resin coated inside the pores. In this way, when an organic solvent is used to improve heat resistance, not only is there an environmental problem, but there is also a factor that inhibits the basic function of the microporous membrane, so there is a disadvantage that the advantage that was intended to be obtained by coating the heat-resistant layer is canceled out.

[0006] To solve this problem, Korean Patent Application Publication No. 10-2016-0041492 proposes a method of forming a coating layer on a porous polymer substrate using an aqueous slurry containing a polyvinylidene fluoride dispersion, inorganic particles, and organic particles. The resulting separator is proposed to be a separator for electrochemical devices with improved adhesion to the porous substrate and excellent heat resistance and strength, but there is still a problem in that the thermal and electrochemical stability of the separator is still insufficient for use in ensuring the safety of the battery, and the battery capacity still needs to be improved.

[0007] Therefore, in order to solve these problems, a new process for producing a separator that is excellent in thermal and electrochemical stability and advantageous in securing pores is required. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Application Publication No. 10-2016-0041492 Summary of the Invention [Problem to be solved by the invention]

[0009] An object of one aspect of the present invention is to provide a secondary battery separator with improved thermal stability, such as low heat shrinkage and high melt rupture temperature.

[0010] Another object of the present invention is to provide a secondary battery separator that can improve the rapid drop and deterioration of the initial life span of a secondary battery due to a low increase rate of resistance in the cell even when the binder content is increased, and can ensure further stability and coating processability.

[0011] Another object of the present invention is to provide a method for manufacturing a separator for a secondary battery, which can prevent pore blockage of a porous substrate when a coating layer of the separator is formed, and can smoothly transfer lithium ions in the manufactured separator, thereby significantly improving electrical characteristics such as a capacity retention rate of the secondary battery.

[0012] Another object of one embodiment of the present invention is to provide a lithium secondary battery including the above-described separator for a secondary battery. [Means for solving the problem]

[0013] According to one aspect of the present invention, there is provided a separator for a secondary battery, comprising: a porous substrate; and a coating layer formed on the porous substrate, wherein the coating layer comprises a plurality of inorganic particles and a binder for binding the plurality of inorganic particles, and the binder may comprise a copolymer of a monomer mixture including an acrylamide-based monomer, a vinylcyan-based monomer, and an acrylic-based monomer having a carboxyl group.

[0014] The monomer mixture may further include an acrylic monomer having a hydroxyl group.

[0015] The copolymer may contain, based on the total weight of the copolymer, 30 to 50% by weight of an acrylamide monomer, 20 to 40% by weight of a vinylcyan monomer, 5 to 20% by weight of an acrylic monomer having a carboxyl group, and 5 to 20% by weight of an acrylic monomer having a hydroxyl group.

[0016] The coating layer may contain 70 to 99.5% by weight of inorganic particles and 0.5 to 30% by weight of a binder based on the total weight of the coating layer.

[0017] The binder may be in a particulate phase.

[0018] The inorganic particles and binder particles may have an average particle size of 10 nm to 2 μm.

[0019] The binder may have a glass transition temperature of 150 to 200°C.

[0020] The copolymer may have a weight average molecular weight of 100,000 to 1,000,000 g / mol.

[0021] A method for producing a separator for a secondary battery according to one embodiment of the present invention includes: a) applying an aqueous slurry containing inorganic particles, a binder, and water onto a porous substrate; and b) heat-drying the aqueous slurry to form a coating layer after the application step. The binder may include a copolymer of a monomer mixture containing an acrylamide monomer, a vinylcyan monomer, and an acrylic monomer having a carboxyl group.

[0022] The monomer mixture may further include an acrylic monomer having a hydroxyl group.

[0023] The copolymer may contain, based on the total weight of the copolymer, 30 to 50% by weight of an acrylamide monomer, 20 to 40% by weight of a vinylcyan monomer, 5 to 20% by weight of an acrylic monomer having a carboxyl group, and 5 to 20% by weight of an acrylic monomer having a hydroxyl group.

[0024] In the step b), the drying temperature may be 60 to 100°C.

[0025] A lithium secondary battery according to one aspect of the present invention may include the above-described secondary battery separator. Effect of the Invention

[0026] The secondary battery separator according to one embodiment of the present invention has significantly improved thermal stability, such as low thermal shrinkage and high melting rupture temperature, and therefore can prevent fire or explosion due to abnormal phenomena such as a sudden temperature rise.

[0027] In addition, the separator for a secondary battery according to an embodiment of the present invention has a low rate of increase in resistance within the cell even when the binder content is increased, thereby improving a rapid decrease in the initial life of the secondary battery and ensuring further stability and coating processability.

[0028] In addition, the separator for a secondary battery according to an embodiment of the present invention can be introduced to improve the performance, such as thermal stability and electrical characteristics, of large-sized lithium secondary batteries applied to electric vehicles and the like. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The present invention will be described in more detail below. However, the following examples are merely for reference in order to explain the present invention in detail, and the present invention is not limited thereto, and can be realized in various forms.

[0030] In addition, unless otherwise defined, all technical and scientific terms have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs. The terms used in the description of this application are merely for the purpose of effectively describing a particular embodiment and are not intended to limit the present invention.

[0031] The present invention relates to a separator for a secondary battery capable of preventing a rapid decrease in thermal stability, electrical characteristics, and life span.

[0032] Conventional secondary battery separators have used non-aqueous or aqueous binders mixed with inorganic particles as a coating layer for improving heat resistance on a porous substrate. The non-aqueous binder uses an organic solvent and a fluorine-based polymer such as polyvinylidene fluoride, which not only causes environmental pollution but also significantly deteriorates the adhesive strength between the porous substrate and the coating layer. To solve this problem, aqueous binders have been proposed, which have the advantages of being environmentally friendly because they use water and being able to reduce the amount of binder used and increase the battery capacity, but have very low thermal stability. In addition, the non-aqueous or aqueous binders have problems such as fire and explosion due to overheating and overload, as organic substances dissolved in organic solvents or binders dissolved in water penetrate the pores of the porous substrate and the movement of lithium ions is restricted by pore blockage. In particular, due to their low thermal stability, it is difficult to deal with overheating and overload, making it difficult for them to function as separators.

[0033] The separator for a secondary battery according to one embodiment of the present invention has significantly improved thermal stability, such as low thermal shrinkage, high glass transition temperature, and high melting rupture temperature, and can prevent fire, explosion, and a sudden decrease in initial life due to abnormal phenomena such as a sudden temperature rise in a lithium secondary battery.

[0034] Specifically, a separator for a secondary battery according to an embodiment of the present invention is a separator including a porous substrate and a coating layer formed on the porous substrate, the coating layer including a plurality of inorganic particles and a binder binding the plurality of inorganic particles, and the binder may include a copolymer of a monomer mixture including an acrylamide-based monomer, a vinylcyan-based monomer, and an acrylic monomer having a carboxyl group.

[0035] In the secondary battery separator according to one aspect of the present invention, even if the binder content is increased to improve adhesion, the increase rate of resistance within the cell is low, thereby improving a rapid decrease in the initial life of the secondary battery and ensuring further stability and coating processability.

[0036] In addition, the separator for a secondary battery according to one aspect of the present invention has properties of low thermal shrinkage, high glass transition temperature, and high melting rupture temperature, and therefore the thermal stability is significantly improved, and it is possible to prevent ignition or explosion due to abnormal phenomena such as a sudden temperature rise in a lithium secondary battery, and to prevent short circuit between electrodes, thereby improving battery stability.

[0037] The separator for a secondary battery according to one embodiment of the present invention contains a copolymer of a monomer mixture containing an acrylamide monomer, a vinylcyan monomer, and an acrylic monomer having a carboxyl group as a binder, and surprisingly has a significantly low thermal shrinkage rate at 160°C, thereby achieving significantly excellent thermal stability and a life-improving effect.

[0038] The monomer mixture may further include an acrylic monomer having a hydroxyl group. When the monomer mixture further includes an acrylic monomer having a hydroxyl group as described above, the thermal shrinkage rate is significantly reduced, and therefore, more excellent thermal stability and life improvement effects can be achieved.

[0039] The copolymer may contain 30 to 50% by weight of an acrylamide monomer, 20 to 40% by weight of a vinylcyan monomer, 5 to 20% by weight of an acrylic monomer having a carboxyl group, and 5 to 20% by weight of an acrylic monomer having a hydroxyl group. More specifically, the copolymer may contain 40 to 50% by weight of an acrylamide monomer, 30 to 40% by weight of a vinylcyan monomer, 5 to 15% by weight of an acrylic monomer having a carboxyl group, and 5 to 15% by weight of an acrylic monomer having a hydroxyl group. By containing a copolymer of the monomer mixture in the above range in the coating layer, the secondary battery separator has a low thermal shrinkage rate at 160°C, and therefore can exhibit significantly excellent thermal stability and life improvement effects.

[0040] Specific examples of the acrylamide monomer include acrylamide, n-methylolacrylamide, n-butoxymethylacrylamide, and methacrylamide, and the like. When the acrylamide monomer is prepared as a copolymer with a vinylcyan monomer and an acrylic monomer having a carboxyl group, it can exhibit excellent wettability with respect to the electrolyte of the secondary battery, and since the binder itself can have porosity, the electrolyte can be sufficiently held in the binder, and the stability of the separator can be improved with excellent ion conductivity. More specifically, when the acrylamide monomer is prepared as a copolymer with a vinylcyan monomer, an acrylic monomer having a carboxyl group, and an acrylic monomer having a hydroxyl group, the above-mentioned physical properties can be further improved.

[0041] Specific examples of the vinylcyan monomer may be acrylonitrile, methacrylonitrile, ethacrylonitrile, or a mixture thereof. When the vinylcyan monomer is prepared as a copolymer with an acrylamide monomer and an acrylic monomer having a carboxyl group, the adhesiveness and adhesion to the porous substrate and inorganic particles can be improved, and mechanical properties such as rigidity and bending strength of the separator can be improved. More specifically, when the vinylcyan monomer is prepared as a copolymer with an acrylamide monomer, an acrylic monomer having a carboxyl group, and an acrylic monomer having a hydroxyl group, the above-mentioned physical properties can be further improved.

[0042] The acrylic monomer having a carboxyl group may be, for example, acrylic acid, methacrylic acid, or a mixture thereof. When the acrylic monomer having a carboxyl group is prepared as a copolymer with an acrylamide monomer and a vinylcyan monomer, the thermal shrinkage rate of the separator at high temperatures is significantly reduced, and the separator has excellent thermal stability and a low rate of increase in discharge resistance, so that a rapid decrease in initial life can be prevented. More specifically, when the acrylic monomer having a carboxyl group is prepared as a copolymer with an acrylamide monomer, a vinylcyan monomer, and an acrylic monomer having a hydroxyl group, the above-mentioned physical properties can be further improved.

[0043] Specific examples of the acrylic monomer having a hydroxyl group include any one or a mixture of two or more selected from 2-hydroxyacrylate, 4-hydroxybutyl acrylate, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-acryloxyethyl-2-hydroxypropyl phthalate, and 2-hydroxy-3-phenoxypropyl acrylate. When the acrylic monomer having a hydroxyl group is prepared as a copolymer with an acrylamide monomer, a vinylcyan monomer, and an acrylic monomer having a carboxyl group, the thermal shrinkage rate of the separator is significantly reduced even at high temperatures, and the separator has excellent thermal stability and a low rate of increase in discharge resistance, so that a rapid decrease in the initial life can be prevented.

[0044] The binder includes a copolymer of a monomer mixture including an acrylamide monomer, a vinylcyan monomer, and an acrylic monomer having a carboxyl group, and thus the thermal stability such as melting rupture temperature is significantly improved in the present invention, and even if the binder content is increased, the increase rate of discharge resistance is low, so that a rapid decrease in initial life and deterioration can be prevented. More specifically, if the monomer mixture further includes an acrylic monomer having a hydroxyl group, the above physical properties can be further improved. Although the reason is unclear, it is believed that this phenomenon occurs because the binder acts as a bridge that induces stronger bonds between particles through chemical bonds or secondary bonds between binders or binders and inorganic particles due to thermal reactions or other reactions of reactive groups such as carboxyl groups or hydroxyl groups of the monomers.

[0045] In a secondary battery separator according to one embodiment of the present invention, the binder may be included in an amount of 0.5% by weight to 30% by weight, based on the total weight of the coating layer (100% by weight), and more specifically, may be included in an amount of 1% by weight to 30% by weight, 2% by weight to 30% by weight, 2% by weight to 20% by weight, 2% by weight to 15% by weight, or 5% by weight to 15% by weight, but is not limited thereto.

[0046] The binder may be a particle phase. When a binder having a particle phase is provided as described above, it is possible to prevent pore blockage of the porous substrate, and the movement of lithium ions is smooth, so that the electrical properties such as the capacity retention rate of the secondary battery can be significantly improved.

[0047] The binder is provided in a particle phase in the aqueous slurry and may have an average particle size of 10 nm to 2 μm, more specifically, 50 to 800 nm. When the binder has the average particle size, it is uniformly dispersed in the aqueous slurry, and when the coating layer is formed, pores of the coating layer are easily formed, and the pore blockage of the porous substrate can be prevented, so that the rapid movement and overload of lithium ions can be prevented.

[0048] The binder may have a glass transition temperature of 150 to 200° C., more specifically, 170 to 200° C., but is not limited thereto. When the binder has the glass transition temperature, the binder has excellent thermal stability at high temperatures of 160° C. or higher, and therefore can have a low thermal shrinkage rate. Even if meltdown of the porous separator occurs, the coating layer is maintained on the porous substrate, and therefore short circuit between electrodes can be prevented, and therefore excellent battery stability can be obtained.

[0049] In the separator for a secondary battery according to one embodiment of the present invention, the copolymer may have a weight average molecular weight of 100,000 to 1,000,000 g / mol, more specifically, the weight average molecular weight may be 100,000 to 500,000 g / mol, but is not limited thereto. When the copolymer has the weight average molecular weight, the copolymer may have uniform dispersibility in an aqueous slurry, and viscosity control may be easy. After being formed as a coating layer, the melt fracture temperature may be improved, and thermal stability may be improved.

[0050] As described above, the separator for a secondary battery according to one embodiment of the present invention has a low resistance increase rate within the cell even when the binder content is increased to improve adhesion, thereby improving the rapid decrease in initial life of the secondary battery and ensuring further stability and coating processability.

[0051] The separator for a secondary battery of the present invention includes a coating layer including inorganic particles and the above-mentioned binder on a porous substrate, thereby reducing the thermal shrinkage rate at high temperatures and significantly increasing the melting fracture temperature, thereby improving thermal stability.In addition, by preventing the blocking of pores in the porous substrate, lithium ions can move smoothly, thereby further improving the capacity retention rate of the lithium secondary battery.

[0052] In addition, the separator for a secondary battery including the coating layer can prevent the movement of lithium ions from being restricted due to pore blockage by providing the binder in a particle phase, and can stably maintain the pores even when pressure is applied.

[0053] In the secondary battery separator according to one embodiment of the present invention, the coating layer may be composed of a combination of inorganic particles and binder particles, and a combination of a porous substrate and binder particles.

[0054] In the secondary battery separator according to one embodiment of the present invention, the inorganic particles may be any one or more inorganic particles selected from the group consisting of alumina, boehmite, aluminum hydroxide, titanium oxide, barium titanium oxide, magnesium oxide, magnesium hydroxide, silica, clay, and glass powder, but are not limited thereto.

[0055] The inorganic particles may be contained in an amount of 70% by weight or more and 99.5% by weight or less, more specifically, 70% by weight or more and 99% by weight or less, 70% by weight or more and 98% by weight or less, 80% by weight or more and 98% by weight or less, 85% by weight or more and 98% by weight or less, or 85% by weight or more and 95% by weight or less, based on the total amount (100% by weight) of the coating layer, but is not limited thereto.

[0056] When the coating layer contains the binder and inorganic particles in the above-mentioned content, the pores of the coating layer can be secured, and the adhesion between the porous substrate and the coating layer or between the inorganic particles can be secured. Even if the binder is contained in a high content, the resistance increase rate in the cell is low, so that a rapid decrease in the initial life of the secondary battery can be prevented, and further stability and coating processability can be secured.

[0057] The binder may be in a particle phase, and the inorganic particles and binder particles may have an average particle size of 10 nm to 2 μm, more specifically, 50 to 800 nm. The inorganic particles and binder particles may have the same or different average particle sizes, but are preferably different for the thermal stability and electrical properties of the separator.

[0058] For the thermal stability and electrical properties of the secondary battery separator, it is preferable that the average particle diameters are different. As a specific example, the inorganic particles and the binder particles may have an average particle diameter ratio that satisfies the following formula 1.

[0059] [Formula 1]

number

[0060] In the above formula 1, R a is the average particle size of the binder particles, and i is the average particle size of the inorganic particles.

[0061] When the inorganic particles and the binder particles are contained in the above average particle size ratio, the thermal stability of the separator can be further improved, and pores generated between the inorganic particles or between the inorganic particles and the porous substrate can be secured by partial adhesion or bonding of the inorganic particles by the binder particles.

[0062] The porous substrate can be any microporous film used in the art, such as a polyolefin resin, and is not particularly limited as long as it has pores and is applicable to batteries, such as nonwoven fabric, paper, and a porous film containing inorganic particles in the internal pores or on the surface of the microporous film.

[0063] The polyolefin resin is preferably a polyolefin resin alone or a mixture, and a specific example may be a mixture of one or more selected from polyethylene, polypropylene, and copolymers thereof. The porous substrate may be a polyolefin resin alone, or may be a substrate made mainly of polyolefin resin and further containing inorganic particles or organic particles. The porous substrate may be used in a laminated form, for example, a polyolefin resin may be formed in multiple layers, and the substrate layer formed in multiple layers may contain inorganic particles and organic particles in the polyolefin resin in any one layer or all layers.

[0064] The thickness of the porous substrate is not particularly limited, and may be 5 to 30 μm. The porous substrate may be a porous substrate produced mainly by stretching, but is not limited thereto.

[0065] The separator for a secondary battery according to one embodiment of the present invention has a very low heat shrinkage rate of 3% or less at 160° C., more specifically, 1.5% or less at 160° C. This makes it possible to prevent ignition or explosion due to abnormal phenomena such as a sudden temperature rise in a lithium secondary battery.

[0066] The secondary battery separator may have a melting rupture temperature of 180° C. or more. More specifically, the melting rupture temperature may be 200° C. or more. The secondary battery separator manufactured according to the present invention has the above physical properties, and thus has a significantly low shrinkage rate at high temperatures, thereby significantly improving thermal stability, and has a low increase rate in discharge resistance even when the binder content is high, thereby improving the lifespan.

[0067] A method for producing a separator for a secondary battery according to one embodiment of the present invention includes: a) applying an aqueous slurry containing inorganic particles, a binder, and water onto a porous substrate; and b) drying the aqueous slurry to form a coating layer after the application step. The binder may include a copolymer of a monomer mixture containing an acrylamide monomer, a vinylcyan monomer, and an acrylic monomer having a carboxyl group.

[0068] The monomer mixture may further include an acrylic monomer having a hydroxyl group in order to improve physical properties.

[0069] The above-mentioned production method makes it possible to produce a separator for a lithium secondary battery having significantly improved thermal stability and capacity characteristics such as the capacity retention rate of the battery, as will be demonstrated in the examples described later.

[0070] To specifically explain the present invention, The step of applying an aqueous slurry containing inorganic particles, a binder, and water onto the porous substrate is a step of applying an aqueous slurry for forming a coating layer having excellent thermal stability and electrical properties onto the porous substrate. The types of the porous substrate, inorganic particles, and binder are as described above, and therefore will not be described here.

[0071] The water may include any one or a mixture of two or more types of water selected from distilled water, purified water, and the like.

[0072] Also, as mentioned above, the binder in the aqueous slurry may be provided in a particulate phase.

[0073] The aqueous slurry may be in a form in which inorganic particles and binder particles are dispersed in water. Specifically, the binder particles may be provided in a form of particles dispersed in water by emulsion or suspension polymerization. The aqueous slurry can be prepared by adding and dispersing inorganic particles in the water in which the binder particles are dispersed.

[0074] The binder particles are formed as a coating layer by emulsion polymerization or suspension polymerization, including a copolymer of a monomer mixture including an acrylamide monomer, a vinylcyan monomer, and an acrylic monomer having a carboxyl group, and the separator for a secondary battery surprisingly has a significantly low thermal shrinkage rate at 160°C, and therefore has a significantly excellent thermal stability and life improvement effect. In addition, the separator for a secondary battery prevents the movement of lithium ions from being restricted due to pore blockage, and the pores can be stably maintained even when pressure is applied. More specifically, when the monomer mixture further includes an acrylic monomer having a hydroxyl group, the above-mentioned physical properties can be further improved.

[0075] The copolymer may contain 30 to 50% by weight of an acrylamide monomer, 20 to 40% by weight of a vinylcyan monomer, 5 to 20% by weight of an acrylic monomer having a carboxyl group, and 5 to 20% by weight of an acrylic monomer having a hydroxyl group, based on the total weight of the copolymer. More specifically, the copolymer may contain 40 to 50% by weight of an acrylamide monomer, 30 to 40% by weight of a vinylcyan monomer, 5 to 15% by weight of an acrylic monomer having a carboxyl group, and 5 to 15% by weight of an acrylic monomer having a hydroxyl group. By forming a coating layer containing a copolymerization agent of the monomer mixture in the above range, the separator has a significantly low thermal shrinkage rate at 160°C, and therefore a coating layer having significantly excellent thermal stability and life improvement effect can be produced.

[0076] In the step b), the drying temperature may be 60 to 100° C. The drying can uniformly dry the coating layer without affecting the physical properties of the porous substrate, and prevent coating defects. The drying step is a step of drying the aqueous slurry applied to the porous substrate with water, and inducing binding between the inorganic particles and the binder to finally form a coating layer.

[0077] According to one aspect of the present invention, there is provided a lithium secondary battery including the separator for a secondary battery described above. The lithium secondary battery may be manufactured by including the separator for a secondary battery according to one aspect of the present invention, a positive electrode, a negative electrode, and a non-aqueous electrolyte solution.

[0078] The description of the secondary battery separator is omitted since it is as described above.

[0079] The positive electrode and the negative electrode may be produced by mixing and stirring a positive electrode active material and a negative electrode active material with a solvent, and if necessary, a binder, a conductive material, a dispersing material, and the like to produce a mixture, and then applying the mixture to a current collector made of a metal material, drying the mixture, and pressing the mixture.

[0080] The positive electrode active material may be any active material commonly used in the positive electrode of a secondary battery, for example, lithium metal oxide particles containing one or more metals selected from the group consisting of Ni, Co, Mn, Na, Mg, Ca, Ti, V, Cr, Cu, Zn, Ge, Sr, Ag, Ba, Zr, Nb, Mo, Al, Ga, B, and combinations thereof.

[0081] The negative electrode active material may be any active material commonly used in the negative electrode of a secondary battery. As the negative electrode active material for a lithium secondary battery, a material capable of lithium intercalation is preferable. Non-limiting examples of the negative electrode active material include lithium (metallic lithium), graphitizable carbon, non-graphitizable carbon, graphite, silicon, Sn alloy, Si alloy, Sn oxide, Si oxide, Ti oxide, Ni oxide, Fe oxide (FeO), and lithium-titanium oxide (LiTiO2, Li4Ti5O 12 ) may be used as the negative electrode active material.

[0082] As the conductive material, any ordinary conductive carbon material can be used without any particular limitation.

[0083] The metal current collector may be any metal that has high conductivity and can be easily attached to the positive electrode active material or negative electrode active material mixture, and is non-reactive within the voltage range of the battery. Non-limiting examples of the positive electrode current collector include foils made of aluminum, nickel, or a combination thereof, and non-limiting examples of the negative electrode current collector may be selected from foils made of copper, gold, nickel, or a copper alloy, or a combination thereof.

[0084] A separator is interposed between the positive electrode and the negative electrode. In addition to the usual winding method, the separator can be applied to a battery by laminating, stacking, or folding the separator and the electrodes.

[0085] The non-aqueous electrolyte contains a lithium salt as an electrolyte and an organic solvent. The lithium salt may be any one that is commonly used in electrolytes for lithium secondary batteries, and Li + X - It can be expressed as:

[0086] The anion of the lithium salt is not particularly limited, and may be F -, Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - Any one or more of the above may be used.

[0087] The organic solvent may be any one or a mixture of two or more selected from the group consisting of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, dipropyl carbonate, dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, sulfolane, gamma-butyrolactone, and tetrahydrofuran.

[0088] The non-aqueous electrolyte can be injected into an electrode structure including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode.

[0089] The shape of the lithium secondary battery is not particularly limited, and may be selected from the group consisting of a cylindrical shape using a can, a square shape, a pouch shape, and a coin shape.

[0090] As described above, the embodiments of the present invention have been described in detail, but those skilled in the art can make various modifications to the present invention without departing from the spirit and scope of the present invention defined in the appended claims. Therefore, modifications of the following embodiments of the present invention do not depart from the technology of the present invention.

[0091] [Physical property measurement method] Heat shrinkage measurement The method for measuring the thermal shrinkage of the separator at 160°C was to prepare a sample by cutting the separator into a square shape with each side being 10cm long, and then measure and record the sample using a camera before the experiment. Five sheets of A4 paper were placed above and below the sample so that the sample was positioned in the center, and the four sides of the paper were fixed with clips. The sample wrapped in paper was left in a hot air drying oven at 160°C for one hour. After leaving it, the sample was taken out and measured using a camera, and the machine direction shrinkage (MD) and transverse direction shrinkage (TD) were calculated using the following mathematical formula 1 and mathematical formula 2, respectively.

[0092] [Mathematical formula 1] Lengthwise shrinkage rate (%) = (length in length direction before heating - length in length direction after heating) x 100 / length in length direction before heating

[0093] [Mathematical formula 2] Width direction shrinkage rate (%) = (width direction length before heating - width direction length after heating) x 100 / width direction length before heating

[0094] TMA and Melt Rupture Temperature Using a METTLER TOLEDO TMA (Thermo-mechanical analysis) device, a 6 mm x 10 mm separator test piece was placed under a weight of 0.015 N and heated at a rate of 5°C / min.

[0095] The TMA melt fracture temperature is the temperature at which fracture of the test piece occurs, and in the case of a sample in which melt fracture does not occur, it is defined as the temperature at which the slope meets the x-axis at its maximum.

[0096] Tensile strength measurement The tensile strength of the separator was measured according to the ASTM D882 standard by measuring the tensile strength of the separator in both the machine direction (MD) and transverse direction (TD), and the lower value of the machine direction and transverse direction was defined as the tensile strength of the separator. Each sample was cut into a rectangular shape with a width of 15 mm and a height of 120 mm, and pulled at a speed of 500 mm / min using a stretching machine. The strength (kgf) at which the separator sample was cut was divided by the width of the sample (15 mm) and the values ​​were recorded and compared.

[0097] Discharge resistance measurement The increase in discharge resistance was confirmed by discharging the battery at 80A for 10 seconds with the battery in SOC50 state, and charging it for 10 seconds, and dividing the change in potential by the current.

[0098] Battery life measurement Each battery manufactured through the above assembly process was charged and discharged 500 times at a discharge rate of 1C, and then a cycle evaluation was performed to measure the discharge capacity and the degree of reduction in the initial capacity.

[0099] Battery thickness measurement In order to check for the lifting phenomenon between the electrode plate and the separator and the deformation of the battery during charging and discharging, the thickness of the battery was measured using a thickness gauge (manufactured by Mitutoyo Corporation) after 500 charge and discharge cycles. The thickness was compared with the thickness before and after charging and discharging to calculate the battery thickness increase rate according to the following mathematical formula 3.

[0100] [Mathematical formula 3] Battery thickness increase rate (%) = (BA) / AX100 A: Thickness of the battery before charging / discharging (mm) B: Battery thickness after charging and discharging (mm)

[0101] Battery nail penetration rating To measure the safety of the batteries, each battery was fully charged to 100% SOC (state of charge) and then subjected to nail penetration evaluation. The nail diameter was 3.0 mm and the nail penetration speed was fixed at 80 mm / min. L1: no change, L2: slight heat generation, L3: leakage, L4: smoke generation, L5: fire generation. L1 to L3 were judged as Pass, and L4 to L5 were judged as Fail.

[0102] Capacity retention rate measurement For the manufactured lithium secondary batteries, the capacity retention rate according to C-rate was measured, assuming that the discharge capacity at each 0.5 C was 100%.

[0103] [Examples 1 to 11 and Comparative Examples 1 to 7: Production of Separators] Example 1 A monomer solution was prepared by mixing 100 parts by weight of ionized water, 0.60 parts by weight of n-dodecyl mercaptan as an emulsifier, and 35 parts by weight of acrylamide, 21 parts by weight of acrylonitrile, 7 parts by weight of acrylic acid, and 7 parts by weight of 2-hydroxyethyl acrylate, which are a monomer mixture.

[0104] A four-neck flask reactor equipped with a stirrer, thermometer, nitrogen inlet, and circulation condenser was prepared, and when the internal temperature of the reactor reached 35°C, the monomer solution and 0.001 parts by weight of benzoyl peroxide and 0.020 parts by weight of sodium formaldehyde sulfoxylate (SFS) as polymerization initiators were added dropwise for 3 hours to proceed with the reaction. Thereafter, 0.0001 parts by weight of benzoyl peroxide and 0.002 parts by weight of sodium formaldehyde sulfoxylate (SFS) were added to remove residual monomers, and the reaction was continued for 2 hours to produce binder particles. The produced binder particles were in the form of latex and had an average particle size of 110 nm.

[0105] 10 parts by weight of the binder particles were added to 100 parts by weight of water and dispersed, and then 90 parts by weight of boehmite (γ-AlO(OH)) (Apyral AOH60, manufactured by Nabaltec) having an average particle size of 500 nm was added and stirred to prepare a uniform aqueous slurry.

[0106] A 9 μm-thick polyolefin microporous membrane product (ENPASS, manufactured by SK Innovation) was used as the porous substrate, and the aqueous slurry was coated on both sides of the substrate using a slot coating die at a speed of 10 m / min, followed by drying and winding.

[0107] After drying, the thickness of the coating layers on both sides was 6 μm.

[0108] Example 2 A separator was manufactured in the same manner as in Example 1, except that 28 parts by weight of acrylamide, 28 parts by weight of acrylonitrile, 7 parts by weight of acrylic acid, and 7 parts by weight of 2-hydroxyethyl acrylate were used as the monomer mixture. The manufactured binder particles were in the form of latex and had an average particle size of 115 nm, and the thickness of the double-sided coating layer after drying was 5.5 μm.

[0109] Example 3 A separator was manufactured in the same manner as in Example 1, except that 21 parts by weight of acrylamide, 28 parts by weight of acrylonitrile, 10.5 parts by weight of acrylic acid, and 10.5 parts by weight of 2-hydroxyethyl acrylate were used as the monomer mixture. The manufactured binder particles were in the form of latex and had an average particle size of 135 nm, and the thickness of the double-sided coating layer after drying was 6 μm.

[0110] Example 4 A separator was manufactured in the same manner as in Example 1, except that 38.5 parts by weight of acrylamide, 24.5 parts by weight of acrylonitrile, 3.5 parts by weight of acrylic acid, and 3.5 parts by weight of 2-hydroxyethyl acrylate were used as the monomer mixture. The manufactured binder particles were in the form of latex and had an average particle size of 125 nm, and the thickness of the double-sided coating layer after drying was 5 μm.

[0111] Example 5 A separator was manufactured in the same manner as in Example 1, except that 21 parts by weight of acrylamide, 21 parts by weight of acrylonitrile, 14 parts by weight of acrylic acid, and 14 parts by weight of 2-hydroxyethyl acrylate were used as the monomer mixture. The manufactured binder particles were in the form of latex and had an average particle size of 120 nm, and the thickness of the double-sided coating layer after drying was 6 μm.

[0112] Example 6 A separator was manufactured in the same manner as in Example 1, except that a monomer mixture of 35 parts by weight of acrylamide, 24.5 parts by weight of acrylonitrile, 7 parts by weight of acrylic acid, and 3.5 parts by weight of 2-hydroxyethyl acrylate was used. The manufactured binder particles were in the form of latex and had an average particle size of 130 nm, and the thickness of the double-sided coating layer after drying was 5.5 μm.

[0113] Example 7 A separator was manufactured in the same manner as in Example 1, except that 35 parts by weight of acrylamide, 24.5 parts by weight of acrylonitrile, 3.5 parts by weight of acrylic acid, and 7 parts by weight of 2-hydroxyethyl acrylate were used as the monomer mixture. The manufactured binder particles were in the form of latex and had an average particle size of 121 nm, and the thickness of the double-sided coating layer after drying was 5.5 μm.

[0114] Example 8 A separator was manufactured in the same manner as in Example 1, except that 2 parts by weight of the binder particles were added and dispersed in 100 parts by weight of water, and then 98 parts by weight of boehmite (γ-AlO(OH)) (Apyral AOH60, manufactured by Nabaltec) having an average particle size of 500 nm was used. The thickness of the double-sided coating layer after drying was 6 μm.

[0115] Example 9 A separator was manufactured in the same manner as in Example 1, except that 5 parts by weight of the binder particles were added and dispersed in 100 parts by weight of water, and then 95 parts by weight of boehmite (γ-AlO(OH)) (Apyral AOH60, manufactured by Nabaltec) having an average particle size of 500 nm was used. The thickness of the double-sided coating layer after drying was 5 μm.

[0116] Example 10 A separator was manufactured in the same manner as in Example 1, except that 15 parts by weight of the binder particles were added and dispersed in 100 parts by weight of water, and then 85 parts by weight of boehmite (γ-AlO(OH)) (Apyral AOH60, manufactured by Nabaltec) having an average particle size of 500 nm was used. The thickness of the coating layers on both sides after drying was 5.5 μm.

[0117] Example 11 A separator was manufactured in the same manner as in Example 1, except that the binder particle latex was prepared to have an average particle size of 350 nm. The thickness of the coating layers on both sides after drying was 5.5 μm.

[0118] Comparative Example 1 A separator was manufactured in the same manner as in Example 1, except that 28 parts by weight of acrylamide, 35 parts by weight of acrylonitrile, and 7 parts by weight of acrylic acid were used as the monomer mixture. The manufactured binder particles were in the form of latex and had an average particle size of 205 nm, and the thickness of the double-sided coating layer measured after drying was 5 μm.

[0119] Comparative Example 2 A separator was manufactured in the same manner as in Example 1, except that 21 parts by weight of acrylamide, 42 parts by weight of acrylonitrile, and 7 parts by weight of 2-hydroxyethyl acrylate were used as the monomer mixture. The manufactured binder particles were in the form of latex and had an average particle size of 175 nm, and the thickness of the double-sided coating layer after drying was 5 μm.

[0120] Comparative Example 3 A separator was manufactured in the same manner as in Example 1, except that 56 parts by weight of acrylamide, 7 parts by weight of acrylic acid, and 7 parts by weight of 2-hydroxyethyl acrylate were used as the monomer mixture. The copolymer was prepared in a form dispersed in ion water, and the thickness of the double-sided coating layer after drying was 6 μm.

[0121] Comparative Example 4 A separator was manufactured in the same manner as in Example 1, except that 56 parts by weight of acrylonitrile, 7 parts by weight of acrylic acid, and 7 parts by weight of 2-hydroxyethyl acrylate were used as the monomer mixture. The manufactured binder particles were in the form of latex and had an average particle size of 120 nm, and the thickness of the double-sided coating layer after drying was 5.5 μm.

[0122] Comparative Example 5 A homogeneous slurry was produced by mixing and stirring 10 parts by weight (based on solid content) of polyvinylidene fluoride binder dissolved at 30% by weight in dimethylsulfoxide (DMSO) and 90 parts by weight of boehmite (γ-AlO(OH)) with an average particle size of 500 nm (Apyral AOH60, manufactured by Nabaltec).

[0123] A 9 μm-thick polyolefin microporous membrane product (ENPASS, manufactured by SK Innovation) was used as the porous substrate, and both sides of the substrate were coated at a speed of 10 m / min using a slot coating die. After drying, the thickness of the coating layer on both sides was 5 μm.

[0124] Comparative Example 6 In 100 parts by weight of water, g A separator was manufactured in the same manner as in Example 1, except that 10 parts by weight of acrylic latex (BM900B, solid content: 20% by weight) with a temperature of -52°C and 90 parts by weight of boehmite (γ-AlO(OH)) (Apyral AOH60, manufactured by Nabaltec) with an average particle size of 500 nm were used. The thickness of the coating layers on both sides after drying was 6 μm.

[0125] Comparative Example 7 In 100 parts by weight of water, g A separator was manufactured in the same manner as in Example 1, except that 15 parts by weight of acrylic latex (BM900B, solid content: 20% by weight) with a temperature of -52°C and 96 parts by weight of boehmite (γ-AlO(OH)) (Apyral AOH60, manufactured by Nabaltec) with an average particle size of 500 nm were used. The thickness of the coating layers on both sides after drying was 5.5 μm.

[0126] [Examples 12 to 22 and Comparative Examples 8 to 14: Production of Lithium Secondary Batteries] (1) Manufacturing of positive electrodes A uniform positive electrode slurry was prepared by adding 94% by weight of LiCoO2 as the positive electrode active material, 2.5% by weight of polyvinylidene fluoride as the adhesive, and 3.5% by weight of carbon black as the conductive agent to the solvent NMP (N-methyl-2-pyrrolidone) and stirring. The slurry was coated on an aluminum foil with a thickness of 30 μm, dried at a temperature of 120°C, and then pressed to prepare a positive electrode plate with a thickness of 150 μm.

[0127] (2) Manufacturing of negative electrodes The negative electrode active material is 95% by weight of artificial graphite, and the adhesive is T g A uniform negative electrode slurry was produced by adding 3% by weight of acrylic latex (BM900B, solid content: 20% by weight) with a temperature of -52°C and 2% by weight of CMC (Carboxymethyl Cellulose) as a thickener to water as a solvent and stirring. The slurry was coated on a copper foil with a thickness of 20μm, dried at a temperature of 120°C, and then pressed to produce a negative electrode plate with a thickness of 150μm.

[0128] (3) Battery manufacturing Pouch-type batteries were assembled by stacking using the prepared positive and negative electrodes and the separators prepared in Examples 1 to 11 and Comparative Examples 1 to 7. An electrolyte solution of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) / dimethyl carbonate (DMC) = 3:5:2 (volume ratio) in which 1M lithium hexafluorophosphate (LiPF6) was dissolved was injected into each assembled battery to manufacture a lithium secondary battery.

[0129] The evaluation results of the separator characteristics of Examples 1 to 11 and Comparative Examples 1 to 7 are shown in Table 1, the evaluation results of the lithium secondary batteries of Examples 12 to 22 and Comparative Examples 8 to 14 are shown in Table 2, and the measurement results of the capacity retention rate according to C-rate of the lithium secondary batteries of Examples 12 to 22 and Comparative Examples 8 to 14 are shown in Table 3. The unit of the capacity retention rate in Table 3 is mAh / g, which indicates the capacity relative to the mass of the positive electrode active material.

[0130] [Table 1]

[0131] As shown in Table 1, the separator of the embodiment in which a coating layer containing binder particles and inorganic particles made of a copolymer of a monomer mixture including an acrylamide monomer, a vinylcyan monomer, an acrylic monomer having a carboxyl group, and an acrylic monomer having a hydroxyl group is formed on both sides of a porous substrate has a lower heat shrinkage rate at 160°C and a significantly increased TMA melt fracture temperature compared to the comparative example, and thus it can be confirmed that the thermal stability of the separator is significantly improved.

[0132] On the other hand, when comparing Example 1 and Example 11, it was confirmed that when the binder particles and inorganic particles have an average particle size ratio that satisfies the above-mentioned formula 1, the thermal properties are further improved and improved thermal stability can be achieved.

[0133] In addition, by comparing Examples 1-3 and 5-7 with Example 4, it was confirmed that when the binder particles are produced in the range of 30 to 50 weight % of acrylamide monomer, 20 to 40 weight % of vinylcyan monomer, 5 to 20 weight % of acrylic monomer having a carboxyl group, and 5 to 20 weight % of acrylic monomer having a hydroxyl group, the thermal stability and separator strength can be improved.

[0134] Furthermore, when Examples 1, 2, 6, and 7 are compared with Examples 3 and 5, it was confirmed that the binder particles exhibited better thermal stability when they contained 40 to 50% by weight of an acrylamide monomer, 30 to 40% by weight of a vinylcyan monomer, 5 to 15% by weight of an acrylic monomer having a carboxyl group, and 5 to 15% by weight of an acrylic monomer having a hydroxyl group.

[0135] In addition, it was confirmed that when the binder was prepared in a form dispersed in an aqueous slurry as in Comparative Example 3, the thermal stability was decreased.

[0136] In addition, it was confirmed that when the conventional polyvinylidene fluoride of Comparative Example 5 and the acrylic polymers with extremely low glass transition temperatures of Comparative Examples 6 and 7 were used for the coating layer, the heat shrinkage rate at 160°C was higher and the TMA melt rupture temperature was lower than those of the Examples. In addition, it was confirmed that the stability of the battery was reduced because it was difficult to prevent a short circuit between the electrodes when shutdown or meltdown of the porous substrate occurred at high temperatures due to low thermal stability.

[0137] [Table 2]

[0138] As shown in Table 2, the lithium secondary battery including the separator of the embodiment in which the coating layer including the binder particles and inorganic particles made of the copolymer of the monomer mixture including the acrylamide-based monomer, the vinylcyan-based monomer, the acrylic monomer having a carboxyl group, and the acrylic monomer having a hydroxyl group is formed on both sides of the porous substrate has low discharge resistance and significantly improved thermal stability, thereby preventing short circuit between electrodes even when the battery is pierced by a nail, and significantly improving battery stability such as the ratio of discharge capacity at the end of battery life to the initial capacity, the change in battery thickness, and the nail piercing stability of the battery.

[0139] On the other hand, when the binder particles and the inorganic particles have an average particle size ratio that satisfies the above-mentioned formula 1, by comparing Example 12 with Example 22, it was confirmed that excellent heat resistance, the ratio of battery life discharge capacity to the initial capacity, the change in battery thickness, and the nail penetration stability of the battery are further increased, and thus it was confirmed that further improved battery stability can be realized.

[0140] Furthermore, when Examples 12-14 and 16-18 are compared with Example 15, it was confirmed that when the binder particles of the present invention are produced in the ranges of 30-50% by weight of an acrylamide monomer, 20-40% by weight of a vinylcyan monomer, 5-20% by weight of an acrylic monomer having a carboxyl group, and 5-20% by weight of an acrylic monomer having a hydroxyl group, they exhibit excellent thermal stability and separator strength, and therefore exhibit further improved battery life and stability.

[0141] Furthermore, when Examples 12, 13, 17, and 18 are compared with Examples 14 and 16, it was confirmed that a binder particle containing 40 to 50% by weight of an acrylamide monomer, 30 to 40% by weight of a vinylcyan monomer, 5 to 15% by weight of an acrylic monomer having a carboxyl group, and 5 to 15% by weight of an acrylic monomer having a hydroxyl group exhibited a more excellent improvement effect on battery life and stability.

[0142] In addition, when the aqueous slurry contained a coating layer that did not contain a particle phase binder, as in Comparative Example 10, the binder penetrated into the pores of the porous substrate, causing pore blockage and restricting the movement of lithium ions, resulting in fires and explosions due to overheating and overload.

[0143] Furthermore, as can be seen from Examples 19 to 21, when the binder particles of the present invention are contained, the rate of increase in discharge resistance is low even when the content of the binder particles is increased, so that a rapid decrease in initial life can be prevented and excellent battery characteristics can be achieved over a long period of time.

[0144] In addition, when the conventional polyvinylidene fluoride of Comparative Example 12 and the acrylic polymers having extremely low glass transition temperatures of Comparative Examples 13 and 14 are used for the coating layer, it was confirmed that when a shutdown or meltdown of the porous substrate occurs at high temperatures due to low thermal stability, it is difficult to prevent a short circuit between the electrodes, and the stability of the battery is reduced.

[0145] [Table 3]

[0146] As shown in Table 3, the lithium secondary battery including the separator of the embodiment in which the coating layer including the binder particles and inorganic particles made of the copolymer of the monomer mixture including the acrylamide monomer, the vinylcyan monomer, the acrylic monomer having a carboxyl group, and the acrylic monomer having a hydroxyl group is formed on both sides of the porous substrate, exhibited a significantly improved capacity retention rate according to the C-rate.

[0147] When the binder particles and the inorganic particles have an average particle size ratio that satisfies the above-mentioned formula 1, it was confirmed that the capacity retention rate according to the C-rate was improved by comparing Example 12 with Example 22.

[0148] In addition, when Examples 12-14 and 16-18 are compared with Example 15, it was confirmed that when the binder particles of the present invention are produced in the range of 30-50% by weight of an acrylamide monomer, 20-40% by weight of a vinylcyan monomer, 5-20% by weight of an acrylic monomer having a carboxyl group, and 5-20% by weight of an acrylic monomer having a hydroxyl group, they exhibit excellent thermal stability and separator strength, and therefore exhibit an improved effect of improving the capacity retention rate due to the improved C-rate.

[0149] Furthermore, when Examples 12, 13, 17, and 18 are compared with Examples 14 and 16, it was confirmed that a better capacity retention rate due to C-rate was observed when the binder particles contained 40 to 50% by weight of an acrylamide monomer, 30 to 40% by weight of a vinylcyan monomer, 5 to 15% by weight of an acrylic monomer having a carboxyl group, and 5 to 15% by weight of an acrylic monomer having a hydroxyl group.

[0150] In addition, it was confirmed that when the conventionally used polyvinylidene fluoride of Comparative Example 12 and the acrylic polymers having extremely low glass transition temperatures of Comparative Examples 13 and 14 were used for the coating layer, the capacity retention rate of the battery was significantly inferior to that of the Examples.

[0151] Therefore, the secondary battery separator of the present invention not only has excellent thermal stability and battery stability, but also has excellent electrical properties such as capacity retention rate, and therefore can exhibit significantly excellent properties when applied to a lithium secondary battery.

[0152] As described above, the present invention has described a separator for a secondary battery, a manufacturing method thereof, and a lithium secondary battery including the same, by giving specific and limited examples. However, this is merely provided for a more general understanding of the present invention, and the present invention is not limited to the above examples. Various modifications and variations are possible from such descriptions by those having ordinary skill in the art to which the present invention pertains.

[0153] Therefore, the spirit of the present invention should not be limited to the described embodiments, and all things equivalent or equivalent modifications to the scope of the appended claims, as well as the scope of the spirit of the present invention, are within the scope of the present invention.

Claims

1. A separator comprising a porous substrate and a coating layer formed on the porous substrate, The coating layer includes a plurality of inorganic particles and a binder that binds the plurality of inorganic particles, The binder comprises a copolymer of a monomer mixture including an acrylamide monomer, a vinylcyan monomer, an acrylic monomer having a carboxyl group, and an acrylic monomer having a hydroxyl group; A separator for a secondary battery, having a machine direction (MD) heat shrinkage rate of 1.8% or less and a transverse direction (TD) heat shrinkage rate of 1.9% or less at 160°C.

2. 2. The separator for a secondary battery according to claim 1, which has a melt-rupture temperature of 180° C. or higher.

3. A separator for a secondary battery as described in claim 1, having a machine direction (MD) heat shrinkage rate of 0.8 to 1.8% and a transverse direction (TD) heat shrinkage rate of 0.9 to 1.9% at 160°C.

Citation Information

Patent Citations

  • Multilayered porous film

    JP2011005670A

  • Slurry for power storage device, power storage device electrode, separator and power storage device

    JP2015022956A

  • Composition for nonaqueous secondary battery porous films, porous film for nonaqueous secondary batteries, and secondary battery

    JP2015162313A

  • Binder for secondary battery porous films, slurry composition for secondary battery porous films, porous film for secondary batteries, and secondary battery

    JP2015185530A

  • Improved isolation plate for lithium-ion batteries and its applications

    JP2015528633A